Optimization Of Ethylene Scavenger Based on KMnO₄, Clay, Activated Charcoal for Delaying The ripening of Red Guava (Psidium guajava, L.) - Silvia, Deli; Arsinta, Dina; Rachmadhan, Fathan (Indonesian Food Science and Technology Journal, 2026)
Red guava (Psidium guajava L.) is a climacteric fruit with high economic and nutritional value, but it has a short shelf life due to high post-harvest ethylene gas production. This causes economic losses for farmers and traders. The use of ethylene scavengers in active packaging is a potential solution to extend the shelf life of horticultural fruits. This study aims to obtain the optimal formulation of an ethylene scavenger based on KMnO₄, clay, and activated carbon to maintain the quality and safety of red guava consumption. The method used was a Completely Randomized Design (CRD) with variations in KMnO₄ + activated charcoal (2g, 6g, 8g) and KMnO₄ + clay (10g, 20g, 30g) concentrations, applied to fruits stored for 0, 8, 12, 16, and 20 days at room temperature. The quality parameters tested included weight loss, moisture content, total soluble solids (TSS), pH, vitamin C content, and organoleptic testing (color, aroma, texture) using a hedonic scale of 1–5. Data analysis was performed using one-way ANOVA followed by the DMRT Multiple Range Test (DMRT) at a 95% confidence level (triplicates). The results showed that ethylene scavengers (KMnO₄ + activated charcoal and KMnO₄ + clay) significantly affected weight loss, TSS, and organoleptic properties, particularly on days 8 to 12 of storage. However, there were no significant differences in moisture content, pH, and vitamin C. This formulation maintained the quality of red guava up to day 12, representing a 50% delay in quality deterioration compared to A0, and delayed spoilage until day 16, corresponding to a 100% extension of shelf life. These findings indicate that the formulation has strong potential as an active packaging to extend shelf life and preserve the quality of red guava.